New Popular Encyclopedia A General Dictionary of the Arts and Sciences, Literature, Biograph, History, Geography etc. Vol-10 - Annandale, Charles (Ed) (New Delhi NBBC Publishers and Distributors, 2014)
Nebula - Petermann